Prevalence, Fate and Effects of Plastic in Freshwater Environments: New Findings and Next Steps - Farhan R. Khan (Toxics, 2020)
At a time when a global pandemic rightly holds our collective attention, environmental issues have taken a backseat to the ongoing battle against Covid-19 [...]